Traumatic Fibular Loss Managed with a Free Vascularized Fibular Graft: A Case Report. Issue 1 (9th January 2022) - Hartnett, Davis A.; Milner, John D.; Salameh, Motasem; Got, Christopher J.; Blankenhorn, Brad D.
Abstract : Case: A 25-year-old man involved in a jet skiing accident experienced a traumatic excision of his distal fibula in conjunction with other lower extremity injuries. He subsequently underwent a reconstruction of his lateral malleolus using an ipsilateral free vascularized fibular graft (FVFG) from his proximal fibular shaft, resulting in a preserved and stabilized ankle joint at 1 year. Conclusion: Traumatic distal fibular excision is a rare injury that can be successfully managed using an FVFG, with fusion of the distal syndesmosis and a symmetric ankle mortise observed at the 1-year follow-up.